A STUDY ON THE ABILITY OF THE SECOND GRADE STUDENTS OF SMAN 1 KUANTAN HILIR IN COMPREHENDING REPORT TEXT - Siparilas, Jun; Ras, Fakhri; K, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study is to find out the ability of the second grade students of SMAN 1 Kuantan Hilir in comprehending report text. This research focuses on students’ comprehending report text in terms of finding main ideas, factual information, the meaning of vocabulary, identifying references and making inferences,.The data were collected using report text test with multiple choice type. The test contained 30 items. The try out was conducted to check the validity and reliability of the test. Based on the research, it was found out that first: the ability of the second grade students in comprehending report text is in the mediocre level with the mean score of 53.13. Second, the students’ mean score in finding the main idea is in good level with the mean score of 66.83, finding the factual information is in mediocre level with the mean score of 58.01, in finding the meaning of vocabulary is in mediocre level with the mean score of 48,90, in finding references is in mediocre level with the mean score of 53.93, in finding inference is in poor level with the mean score of 37.98. As a conclusion, the highest score obtained by the students is in finding main ideas with the mean score of 66.83 which is categorized into good level, and the lowest score that the students got is in finding inference ,with the mean score of 37.98 which is categorized into poor level. This results of this study suggest that the students to learn more about comprehending report text.Keywords : Study, Ability, Report text.